Impact of reactor configuration and relative operating conditions on volatile fatty acids production from organic waste. Issue 1 (31st December 2022) - Rossi, Elena; Pecorini, Isabella; Panico, Antonio; Iannelli, Renato
ABSTRACT: In the last decades, the worldwide interest in volatile fatty acids (VFAs) as basic elements for many industrial applications has been growing as fast as their market demand. Traditional production of VFAs from crude oil is unsustainable because of its environmental impact, therefore alternative solutions have been studied. The most promising solution has resulted in the VFAs production from organic waste based on biological processes thanks to the incoming environmental and economic benefits. In this scientific context, the state of current knowledge has not reached yet a satisfying level of comprehensiveness and it is mainly based on studies conducted at lab and pilot scale. Under the perspective to gain more knowledge and thus to promote an efficient as well as consolidated production of VFAs according to the key issues of the circular economy, a systematic and detailed study dealing with the impact of reactor configuration and relative operating conditions on biological VFAs production has been conducted. This step is a necessary condition to scale up the process and achieve its complete industrialization. According to this perspective and on the basis of the most recent findings from the international literature, the present review paper reports, as the main result of data elaboration, a novel one-to-one correspondence between organic wastes and reactor configurations having as target the VFAs yield enhancement. GRAPHICAL ABSTRACT: UF0001